Entropy as a marker of physiological transition during pediatric cardiopulmonary exercise testing - O’Hara, Kaleigh; Brown, Donald E.; Cooper, Dan M.; Stehli, Annamarie; Radom Aizik, Shlomit; Kupperman, Natalie (Frontiers in Physiology, 2025)
This research analyzed the sample entropy (SampEn) of breath-by-breath cardiopulmonary exercise testing (CPET) data from 170 healthy pediatric participants (85 males) 8 to 18-years-old, using a Bayesian statistics approach. SampEn measures the complexity of time series data, providing quantitative insight into the predictability of breathing patterns in pediatric participants. To address non-stationarity, signals were differenced prior to SampEn calculation. In addition to sex and age group comparisons, we examined SampEn before and after the midpoint of each participant’s CPET to assess how SampEn changes as exercise intensity increases. We corroborated previous findings that SampEn decreases in the later half of CPET for healthy pediatric participants for oxygen uptake (V̇O2), carbon dioxide output (V̇CO2), ventilation (V̇E), and heart rate (HR). Females tended to have higher SampEn than their male counterparts, with a statistically significant difference between the sexes in older participants for V̇O2, V̇CO2, V̇E, HR, and respiratory rate (RR). Age-related findings included: significantly higher SampEn in younger males compared to older males for V̇O2 and V̇E and older female participants had a higher SampEn in older females compared to younger females for HR. These findings support SampEn as a sensitive, non-invasive marker of physiological transition during pediatric CPET, with potential applications in exercise physiology research and clinical assessment.